High Rejection Sensitivity in Patients With Somatoform Pain Disorder - Nacak, Yeliz; Morawa, Eva; Erim, Yesim (Frontiers in Psychiatry, 2021)
Objective: Rejection sensitivity (RS) is often associated with mental disorders, but as yet has not been investigated in patients with somatoform pain disorder (SPD). The main of the study was to explore the degree of RS in patients with SPD compared to healthy controls. In addition, we examined factors associated with RS and the moderator effect of SPD. Methods: 65 patients with SPD (confirmed by Structured Clinical Interview, SCID-I) and 65 age- and gender-matched healthy controls participated. Rejection Sensitivity Questionnaire (RSQ), Patient Health Questionnaire (PHQ-9, PHQ-15), Relationship Scale (ReSQ), Essen Trauma Inventory (ETI) and the Childhood Trauma Questionnaire (CTQ) were applied. Multi-ple linear regression analysis was performed. Results: The level of RS was significantly higher in patients with SPD compared to healthy controls. (M=10.30, SD=5.64; M=6.13, SD=2.50; p<.001; d=.95). Higher levels of depressive symptoms (p<.001), childhood adversities (p<.001) and the insecure attachment style (p=.007) were related with higher levels of RS. No significant moderation effect was detected. Conclusions: Patients with SPD are highly sensitive to social rejection. In addition, insecure attachment style as well as depressive symptoms and childhood adversities seem to play an im-portant role for RS. Therapeutic interventions of SPD should target RS and the factors, which strengthen them.